INTRAUTERINE INFECTION (World Bulletin of Public Health, 2024)
Currently, against the background of a low level of infant mortality in our country, there remains a high incidence in the structure of infections specific to the early neonatal period, among which intrauterine infections occupy a leading position. Intrauterine infection of the fetus and newborn plays a significant role in the development of infectious and inflammatory diseases